PENGARUH PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium ascalonicum L) - I Made Sukerta; I Putu Sujana; I Gusti Ayu Diah Yuniti; Yohanes Rodrian (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2024)
This study is entitled "The Effect of Dosage of Chicken Cage fertilizers on the growth and results of the onional plant (Allium Ascalonicum L)". The needs of society against onions will continue to increase along with the increase in the population. The purpose of this research is to know the effect of dose of chicken cage fertilizer against growth and results of onion crops. This study uses randomized design (RAK) and was conducted on June 05 until 26 August 2021 consisting of 6 treatment and each treatment was repeat 4, thereby 24 experimental units. P0 = No cockpils of chicken, P1 = 3t/ha chicken chief fertilizer, P2 = 6t/ha pink cage fertilizer, P3 = 9t/ha pink sufferell, P4 = 12t /ha pink feather cake, p5 = 15t/ha chicken cage fertilizer. The treatment of chicken coexisthood is a real effect of parameters of the number of leaves and influentials are very real to the high plant (cm), the number of per cent plates (bh), the amount of tubers per plant (bh), fresh weight of the plant (g), dry weight of ginnous per bamps per plant. (G), and dry weight obs burnt per plant (g) and dosage of dye of chicken cage fever 12 t/ha gives the growth and best results to fresh weight of tuling per plant, 55.88 g, dry weight of burnt per gulf plant is 52.30 g and dry weight of obs bulbers 27.59 g